IgG4 anti-neurofascin155 antibodies in chronic inflammatory demyelinating polyradiculoneuropathy: Clinical significance and diagnostic utility of a conventional assay - Kadoya, Masato; Kaida, Kenichi; Koike, Haruki; Takazaki, Hiroshi; Ogata, Hidenori; Moriguchi, Kota; Shimizu, Jun; Nagata, Eiichiro; Takizawa, Shunya; Chiba, Atsuro; Yamasaki, Ryo; Kira, Jun-ichi; et al. (Journal of neuroimmunology, 2016)
We aimed to validate the diagnostic utility of enzyme-linked immunosorbent assay (ELISA) for the detection of anti-neurofascin (NF) 155 antibody in 191 patients with chronic inflammatory demyelinating polyneuropathy (CIDP). Human NF155-based ELISA clearly distinguished between anti-NF155 antibody-positive and -negative sera. Fifteen CIDP patients (8%) were IgG4 anti-human NF155 antibody-positive, which were confirmed by western blot, cell-based assay and immunohistochemical study. None of disease controls or healthy subjects had positive results. Clinical presentation of IgG4 anti-NF155 antibody-positive patients was consistent with those in previous reports. This ELISA combined with determination of the IgG4 subclass is useful in screening for anti-NF155 antibodies. [Display omitted] •Anti-Neurofascin155 antibody was measured in CIDP patients by multiple methods.•The diagnostic utility of human NF155-based ELISA for screening is validated.•Western blot and CBA are useful for confirmation of positive results in ELISA.•Development of the optimal treatment will require gathering of more information.